Accounting for Cryptocurrencies* - Anderson, Chelsea M.; Fang, Vivian W.; Moon, James R.; Shipman, Jonathan E. (Journal of Accounting Research, 2026)
ABSTRACT This paper explores U.S. public firms’ cryptocurrency holdings and accounting practices from 2013 to 2022 against the backdrop of the recently enacted crypto accounting rule, ASU 2023‐08. Descriptive analyses suggest exponential growth in corporate crypto holdings and significant variation in crypto accounting practices, underscoring the rule's necessity. Hypothesis tests using the pre‐rule data reveal three insights with direct relevance to the rule. First, firms appear to view crypto assets more akin to investments than intangible assets, consistent with the rule's mandate of the fair value model. Second, Big 4 auditors steer firms toward the impairment model and less detailed presentation choices. This conservative approach is unlikely to meet the new rule's goal of providing the most decision‐useful information. Third, increased liquidity of crypto markets prompts the use of the fair value model and a more detailed presentation, consistent with the rule's focus on more actively traded tokens. However, within our sample, we find some evidence consistent with fair value reporting increasing stock return volatility and no evidence that it enhances earnings informativeness.